Classroom Action Research: Improving Students Speaking Skills Through Role Play Technique - Andien, Andien Aisyah Putri; Leil Badrah Zaki (English Language Education, Universitas Internasional Batam, 2025)
This study investigates the effectiveness of role play in improving students’ speaking skills and explores the challenges and strategies associated with its implementation. Employing Classroom Action Research (CAR) as the methodology, the study involved 19 students over three weeks, incorporating pre-tests, role play activities, and post-tests. The results revealed significant improvements in students’ speaking abilities, with the average score rising from 27.2 to 42. Pronunciation, fluency, and comprehension improved from the “poor” to “fair” category, while vocabulary and grammar showed progress but remained “poor.” The role play activities, based on realistic scenarios, enhanced students’ confidence and interactive communication skills. Data from rubrics, observations, and questionnaires supported these findings, confirming the technique’s effectiveness. However, the study highlights the need for additional strategies to address persistent weaknesses in vocabulary and grammar. These findings contribute to practical teaching methods, offering insights into integrating role play to foster more effective communication in diverse educational settings.